2009
DOI: 10.1016/j.jpain.2008.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Endothelin Receptors and Pain

Abstract: In this paper we review the biochemistry, second messenger pathways and hetero-receptor coupling that are activated by ET receptors, the cellular physiological responses to ET receptor activation, and the contribution to pain of such mechanisms occurring in the periphery and the CNS. Our goal is to frame the subject of endothelin and pain for a broad readership, and to present the generally accepted as well as the disputed concepts, including important unanswered questions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
113
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(118 citation statements)
references
References 256 publications
(320 reference statements)
4
113
0
1
Order By: Relevance
“…One gene was Mitogen-activated protein kinase 1 (Mapk1), a signaling molecule that regulates the production of cytokines and cytotoxic enzymes that have been implicated in RA pathogenesis. In agreement with our results, Mapk1 is induced through ETA and ETB receptors, and it mediates important peripheral functions of ETs, including DNA synthesis, mitogenesis, and the activation of vascular smooth muscle [40,41]. Chemokine (C-C motif) receptor 2 (Ccr2) and chemokine (C-C motif) receptor 5 (Ccr5), which along Fig.…”
Section: Discussionsupporting
confidence: 91%
“…One gene was Mitogen-activated protein kinase 1 (Mapk1), a signaling molecule that regulates the production of cytokines and cytotoxic enzymes that have been implicated in RA pathogenesis. In agreement with our results, Mapk1 is induced through ETA and ETB receptors, and it mediates important peripheral functions of ETs, including DNA synthesis, mitogenesis, and the activation of vascular smooth muscle [40,41]. Chemokine (C-C motif) receptor 2 (Ccr2) and chemokine (C-C motif) receptor 5 (Ccr5), which along Fig.…”
Section: Discussionsupporting
confidence: 91%
“…For the inducible null mice this finding is highly surprising because it suggests that ET1's proalgesic/algogenic effect is fully dependent on TRPV4 in keratinocytes. Although previous studies had shown that ET1 is sufficient to elicit nocifensive behavior (66,67), the elimination of ET1's proalgesic/algogenic effect in iKO mice was completely unexpected given that both ET(R)s and TRPV4 are expressed by sensory afferents (63), all of them unaffected in tam-treated iKO mice.…”
Section: +mentioning
confidence: 96%
“…ET(R)s were suitable candidates because they are known to function in pain signaling (63) and because their cognate peptide ligand, endothelin-1 (ET1), is elevated when keratinocytes are exposed to UVB (64). When 1°MK were exposed to ET1, they exhibited a significant increase in UVB-induced Ca 2+ signaling (Fig.…”
Section: +mentioning
confidence: 99%
“…The painful effects of ET-1 administration are linked to its binding to the endothelintype A receptor found on nociceptors. [73,74] The interaction of ET-1 and ETA receptors can induce nociceptor activation in pre-clinical studies of normal subjects. [71,75] ET-1 subcutaneous administration was found to activate C-fibers and A TMfibers in rat sciatic nerve in a dose-dependent manner.…”
Section: Potential Mechanisms Of Scd-associated Painmentioning
confidence: 99%